The Litchi wine fermentation process by the yeast strain Saccharomyces cerevisiae LC3 - Kim Nhung, Dinh Thi (Academia Journal of Biology, 2014)
In the pulp composition of Litchi chinensis Sonn., there are sugar: 164 g/l; acid: 5.1g/l; H2O: 83%; ash: 0.5%; pH = 3.8, optimum for the fermentation process of litchi wine. The litchi fruits are popular materials in the Bacgiang and Haiduong provinces. Every year, their yield is much larger than the consumption demand in the markets, therefore the processing techonology after harvest is an urgent need. For this purpore, we have isolated and chosen the yeast strain Saccharomyces cerevisiae LC3 which was used for the fermentation process of litchi wine. Our research was on the imvestigation of the effects of some envirormental elements on the growth and development of this yeast strain S. cerevisiae LC3 in the fermentation process of litchi wine, which involved in identifying the development of motive sugar: 250 g/l, pH: 3.8-4.2: strains: 10-15%. After that, we have carried out the fermentation process in the laboratory with good results and the fermentation process of litchi wine.